2010
DOI: 10.1038/oby.2009.281
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Weight Loss and Weight Loss Maintenance in Middle‐aged Women

Abstract: Long-term behavioral self-regulation is the hallmark of successful weight control. We tested mediators of weight loss and weight loss maintenance in middle-aged women who participated in a randomized controlled 12-month weight management intervention. Overweight and obese women (N = 225, BMI = 31.3 ± 4.1 kg/m 2 ) were randomly assigned to a control or a 1-year group intervention designed to promote autonomous self-regulation of body weight. Key exercise, eating behavior, and body image variables were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
370
7
30

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(438 citation statements)
references
References 68 publications
(88 reference statements)
31
370
7
30
Order By: Relevance
“…time, about 40-60 % of the adult population in Western countries is attempting to lose or maintain weight (51) .…”
Section: Discussionmentioning
confidence: 99%
“…time, about 40-60 % of the adult population in Western countries is attempting to lose or maintain weight (51) .…”
Section: Discussionmentioning
confidence: 99%
“…In weight regainers, it has also been shown that self-monitoring of food intake and weight control decline over time (3) . According to Teixeira et al (17) lowering emotional eating and adopting a flexible dietary restraint pattern are critical factors for sustained low weight status. Therefore, for long-term success, interventions must also be effective in promoting exercise, intrinsic motivation and self-efficacy.…”
Section: Potential Determinants Of Continued Low Weight Status Aftermentioning
confidence: 99%
“…Although there are a few exceptions, which also suggest the importance of building self-efficacy (e.g., perceptions of ability and competence) and addressing eating in response to emotional cues [24,25], there is little actionable research on theory-based psychosocial factors that might influence success at maintaining weight management behaviors. Analyses of dynamic patterns of changes in psychosocial correlates of eating and physical activity trajectories in participants who were unsuccessful at maintaining their weight loss might be especially instructive beginning just after the time when most weight loss is expected (e.g., after the initial 6 months of treatment [1][2][3]).…”
mentioning
confidence: 99%
“…Thus, the aim of this preliminary, small-sample study was to develop a better understanding of changes within malleable psychosocial factors as they relate to their association with changes in fruits/vegetable consumption, intake of sweets, and physical activity outputs after the completion of a 6-month period of expected weight loss. Based on theory [16,22,23] and previous research over primarily brief time frames [11,25], changes in self-regulation, self-efficacy, mood, and emotional eating were incorporated as predictors of behavioral changes within this research because of their respective roles in (a) overcoming inevitable life-related barriers, (b) perceiving success that motivates persistence, (c) establishing a positive mental climate that is advantageous for persistence, and (d) overcoming emotionbased triggers for lapses into past unproductive eating behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation